2020
DOI: 10.1080/01416200.2020.1713049
|View full text |Cite
|
Sign up to set email alerts
|

Religious education teachers’ perspectives on character education

Abstract: This article presents the findings of a qualitative interview study undertaken with RE teachers (n=30), working in English schools with secondary status. Despite recent policy interest in character education, there is a lacuna of information about the extent RE contributes to character education. The present study focuses on teachers' perspectives on virtue literacy, a theme identified across participants in response to open-ended prompts about RE, religion and character. The participants in the sample hold di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 13 publications
0
15
0
7
Order By: Relevance
“…Sebuah penelitian mengenai perspektif guru agama tentang kontribusi religious education terhadap pendidikan karakter di sekolah bahwa pendidikan agama memiliki andil dalam pembentukan karakter. Meskipun pada beberapa sekolah yang berbasis non-agamis terdapat perbedaan pendapat mengenai hal itu (Metcalfe and Moulin-Stożek, 2020 terutama di kalangan anak muda. Beberapa langkah yang dapat diberikan terutama untuk tindakan pencegahan melalui keluarga dan lingkungan pendidikan.…”
Section: Kedua Melalui Pendidikan DI Sekolahunclassified
“…Sebuah penelitian mengenai perspektif guru agama tentang kontribusi religious education terhadap pendidikan karakter di sekolah bahwa pendidikan agama memiliki andil dalam pembentukan karakter. Meskipun pada beberapa sekolah yang berbasis non-agamis terdapat perbedaan pendapat mengenai hal itu (Metcalfe and Moulin-Stożek, 2020 terutama di kalangan anak muda. Beberapa langkah yang dapat diberikan terutama untuk tindakan pencegahan melalui keluarga dan lingkungan pendidikan.…”
Section: Kedua Melalui Pendidikan DI Sekolahunclassified
“…Character is defined as a behavior, disposition, the properties of nature, morals, or virtues that distinguish a person from others (Henry, 2018;Metcalfe & Moulin-Stożek, 2020). Meanwhile, the teenager is a time when humans are in their dozens of years (teens).…”
Section: A Means Of Preaching the Gospelmentioning
confidence: 99%
“…Education is a process that was aware of its goals, and the point is that education is carried out by predetermined goals (Metcalfe & Moulin-Stożek, 2020). John Dewey (in Wiradimadja, 2019) stated that education is: "One of the sustainable social endeavors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…He found that character education approach that takes into account the intersubjective relationships in schools and the broader social context in which characters can be formed [16]. Metcalfe and Moulin (2020: 10) found the importance of educator's education about indications occurred at schools that support the character education movement develops student character and moral virtue [17]. Attempt to involve parents as partners in character education programs in educational institutions [18].…”
Section: Previous Studies Related To the Impact Of Art Education Withmentioning
confidence: 99%